The Effect of Acupressure at Meridian Points BL67 (Zhiyin) and LI4 (Hegu) on Labor Progress in Primigravida Mothers During the Active Phase of the First Stage of Labor - Nathasia Elga Haryono; Via Wiyana; Martine Agustina Meha; Resha Astari (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
According to the World Health Organization (WHO), approximately 75% of all maternal deaths are caused by various types of complications, one of which is prolonged labor. One non-pharmacological approach that can be used to address this issue is acupressure therapy at the BL67 and LI4 meridian points. The aim of this study was to evaluate the progress of labor in primigravida mothers by comparing the effectiveness of acupressure at the BL67 and LI4 points.This research employed a quasi-experimental method with a post-test only design. A total of 40 primigravida mothers in the active phase of the first stage of labor were evenly divided into two groups: 20 participants received acupressure at the BL67 point and the other 20 at the LI4 point. Data analysis was conducted using an independent sample t-test.The results showed that the significance value for the duration of labor progress in the active phase of the first stage was 0.199, which is greater than the significance threshold of 0.05. Therefore, the null hypothesis (H?) was accepted, indicating that there was no statistically significant difference in the average duration of labor between the group receiving acupressure at BL67 and the group receiving it at LI4.In conclusion, acupressure at both the BL67 and LI4 points can be considered an effective non-pharmacological method to support labor progress.